Quiet Quitting among Generation Z Employees: A Phenomenological Study in the Indonesian Workplace - Tenri Sayu Puspitaningsih Dipoatmodjo (Malaqbi Publisher, 2026)
Quiet quitting, defined as limiting work performance strictly to contractual obligations without voluntary extra-role behavior, has emerged as a significant organizational challenge in post-pandemic workplaces. This qualitative phenomenological study explores the lived experiences of Generation Z (Gen Z) employees in Indonesia, examining how they define, justify, and enact quiet quitting (QQ) behaviors across diverse industry sectors. Drawing on semi-structured in-depth interviews with 12 Gen Z employees from startup, banking, and creative industries, the study employed Braun and Clarke's (2006) six-phase thematic analysis. Four core themes emerged: (1) work-life boundary protection, (2) emotional withdrawal as self-preservation, (3) minimum-effort behavior as rational adaptation, and (4) psychological contract violation. Findings indicate that QQ in Indonesia is not simply workplace disengagement but a culturally mediated, intentionally strategic response to systemic organizational failures, particularly insufficient recognition, poor managerial communication, and incompatible work cultures. These results have implications for human resource management practice, managerial competency development, and organizational policy design in Indonesian workplaces.